Determinación de bacterias en los cepillos dentales utilizados por niños de 4 años de edad del Centro Infantil Municipal Mercado Centro Comercial # 2, 2018 - 2019 - Quezada Salazar, Andrés Esteban (2019)
The present research work is focused on the knowledge and identification of different bacteria that are stored in the toothbrush, for this purpose the main objective was: To evaluate the bacterial contamination of the toothbrushes used by 4 years old children of Centro Infantil Municipal Mercado Centro Comercial # 2. In addition to identify the conditions that favor the development of the different microorganisms found. The type of study is observational, analytical and cross-sectional, same that allowed to determine the existence of different kinds of bacteria. To carry out this study, 25 toothbrushes were delivered to children of Centro Infantil Municipal Mercado Centro Comercial # 2, and after one month they were removed. A microbiological analysis was carried out in MEDILAB laboratory. The data was processed in the SPSS statistical analysis program. Obtaining as relevant results the presence of bacteria such as: Streptpcoccus spp 45.2% (19) Echerichia coli 23.80% (10). Klebsiella pneumoniae 16.7% (7) Pseudomonas spp 7.2% (3) Streptpcoccus B 2.4% (1) Staphylococcus spp 2.4% (1) Micrococcus spp 2.4% (1). The most prevalent bacterium was Streptococcus spp, and its presence is due to different storage conditions observed such as: location of the toothbrush, distance with respect to the toilet, way of storage, care of the toothbrush, the frequency of brushing and the presence of some common disease in children. Keywords: Pollution, identification, microorganism, toothbrush.